EVALUASI PEMBANGUNAN IKN BERDASARKAN KEBERHASILAN SPONGE CITY DI CHINA - Keliwar, Khairi Ahza Hail; Rinda, Zuhalfi Akbar; Nouri, Mh Nateq; Alvianti, Vivian; Putri, Dhea Ananda (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
The relocation of the capital city (IKN) to East Kalimantan, as regulated by Law Number 3 of 2022, will drive massive regional development. However, the province of East Kalimantan, which is prone to flooding, requires a special approach such as implementing the Sponge City concept to minimize flood risks and support the sustainable development of IKN. This research aims to provide recommendations for effectively implementing Sponge City infrastructure to address flood issues in IKN through a comparative study of the application of the Sponge City concept in China. Secondary data is used in this research, covering variables such as topography, climate, area size, rainfall, annual flood frequency, and the objectives of the capital city. The methods used include a comparative study with cluster analysis to compare city characteristics, performance analysis to assess effectiveness, and descriptive analysis to provide recommendations for the implementation of Sponge City in IKN. The results indicate that Nanjing and Haikou in China serve as benchmarks, with retention ponds, green roofs, and wetlands being effective infrastructures for flood management. Wetlands are considered the most economical and effective infrastructure to implement in IKN due to their lower maintenance costs compared to retention ponds and green roofs.